Gender-collaborative training in elite university sport: Challenging gender essentialism through integrated training in gender-segregated sports - Ogilvie, M. F.; McCormack, Mark (International Review for the Sociology of Sport, 2020)
Competitive teamsport at university level is predominantly segregated by gender in many western countries, despite concerns that gender segregation in sport can perpetuate sexism and gender inequality. While policies and activities seek to challenge sexism and gender inequality, the use of gender collaboration within a gender-segregated system as a method to achieve this has received little attention. In this article, we draw on a year-long ethnography of elite sport and 48 in-depth interviews with elite male and female athletes at a British university to explore the impact of various forms of gender mixing during training, which we call ‘gender-collaborative training’. While men’s and women’s teams competing against each other in practice matches resulted in gender-essentialist narratives attributing difference to biology, gender-integrated practices and workouts provided opportunities for men and women to train together without the gendered sport-specific associations that can reproduce sexism. We call for gender-collaborative training to be adopted by gender-segregated teams, and suggest that where there is resistance to any integration, teams start with mixed physical workouts and progress to mixed sport-specific training and then mixed competitive training. © The Author(s) 2020.
7 citations (Crossref) [2023-10-31] WOS:000599892600001
Keywords: adult; article; dept.soc; ethnography; female; human; interview; male; narrative; peer-reviewed; sexism; training